Relationship Between Culture and Poetic Communication - Milosav Ž. (Stylistyka, 2002)
In order to answer the question about the relationship between culture and poetic communication, the author has assumed that poetic language is а schematic abstraction which functions according to the system of poetic signs that produce а large amount of in formation. Therefore, the poetic language achieves а special kind of communication. The author has concluded that this is only feasible when we have an ideal creator, and ideal code, and an ideal recipient in an ideal cultural community - а community with the great est level of cultural development - and not only this. The level of productivity of the poetic communication, in the first place, depends on the creator himself who is а maker of the poetic work, on his knowledge of the paradigmatic axis (an axis of symbol repertoire and rules - the axis of selection), and the syntagmatic axis (an axis 011 which symbols аге combined forming more complicated syntagmatic chains), the creator’s art of encoding the poetic material (even the poetic codification and deviations from it), because the creator is аblе to regulate each and every aspect of his message on different levels of linguistic structure: phonetic, phonological, morphological, lexical, syntactic and textual. On the other hand, the author says that the achieved level of poetic commnnication nоt only de pends on the system of informational and communicative conventions used bу the creator (sender) who wants to show his thoughts, wishes and his attitude towards the outside world, but also on the recipient’s knowledge, his system of psychological expectations, spiritual attitndes, his experience, moral principles, culture, and especially on his ability to decode аn encoded message respecting the rules of the poetic code. In а specific case, the level of poetic communication depends on the specific author, specific code and the specific recipient. Having all this in mind, the author has come to the conclusion that culture and poetic communication are in positive correlation. ln other words, the higher the cultural level of the sender and the recipient of the poetic message, the higher the level of communication.